Beyond the Ethnic Vote: Shifting Determinants of the Electoral Behavior of Transylvanian Hungarians. Issue 2 (4th March 2019) - Kiss, Tamás
Abstract : This study investigates the determinants of electoral behavior in the context of ethnic bloc voting through exploring the case of Hungarians in Transylvania. There is a remarkable lack of systematic micro-level analyses of the electoral behavior of this minority group. The study discusses the impact of both expressive and instrumental motivations on the voting behavior. The article contributes to the literature of this field in two ways. First, it tests different models of ethnic voting in post-Communist context. Second, it argues that electoral motivations can change over time, and in different phases of the historical process of minority mobilization, different motivations can lead to the (seemingly similar) outcome of ethnic bloc voting.